MEMBANGUN JARINGAN ULAMA YANG DITERAPKAN DALAM GERAKAN MUHAMMADIYAH - Silawati, Silawati; Nurdiniyah, Hayyun (STAI Darul Qalam Tangerang, 2023)
The Ulama network is a journey to seek knowledge that is very closely related to scientific traditions. This tradition originates from the scientific journey of the companions after the death of the Prophet to collect and record hadith. Developments seen from scientific journeys not only provided a collection of the Prophet's Hadith, but also encouraged a